The business of agricultural business services: Working with smallholders in Africa - Heemskerk, Willem; Kahan, David; Wongtschowski, Mariana; Belt, John (CTA / Royal Tropical Institute / FAO, 2013)
If African smallholders are to run their farms as sustainable and profitable businesses they must understand how markets work. To do so they need advice from others; they need services. Agricultural business development services – the subject of this book – include technical advice on production and postharvest handling, marketing ideas, business planning, links with buyers and credit, and help with contracts and standards. Carefully illustrated throughout, the text looks at how 12 business service providers from across Africa run their businesses. Based on their experiences, it proposes a new, needs-driven approach.